Radiological Assessment of Mandibular Retromolar Canal (MRMC) Using CBCT-Radiographs in a Sample of Iraqi Patients - Jamal Abid Mohammed; Zainab H. Al-Ghurabi (College of Dentistry/ University of Baghdad, 2016)
Background: Because of its clinical and surgical importance and lack of precise information about this rare and important anatomical landmark, this study was designed to detect the presence, configurations and length of Mandibular Retromolar Canal (MRMC) with aid of CBCT visualization. Materials and methods: In this retrospective study the data was obtained from Specialist Health Center in AL-Sadder city in Baghdad for (100) patients with 200 inferior dental canal, all of them referred to CBCT scan (Kodak 9500, French origin). The scanning was done with tube voltage 90 kVp, tube current with 10mA and exposure time was 10 s., the field of view was measured with 5cm x 3.7cmwith 0.03mm voxel size Results: In the present study the prevalence of MRMC was 12% , 2 patients have ( two ) bilateral MRMC and 10 patients have a unilateral canal, there was asignificant difference between two sides (left and right), the right side was 64.29% and left 35.71%, regarding to gender also there was a significant difference , female 33.3% and male 66.7%. In this study there were three types of MRMC and there was a significant difference between them, the mean length (hight) was 11.78 mm and mean horizontaldistance from canal to distal surface of the second molar was 18.5 mm. Conclusions: MRMC also detectedin this study within the global percentage and configurations and should be taken with consideration in oral surgical procedures and radiological interpretations